Chemical health risk assessment at private medical laboratory / Mohammad Fauzan Mohammad Rohmatullah - Mohammad Fauzan , Mohammad Rohmatullah (2018)
The use of chemicals in laboratories need proper safety management to protect staff from chemical health risk during performing their work. The purpose of this study is to identify and evaluate the level of exposure of chemicals towards staffs which working in the laboratory. A private medical laboratory was selected and chemical health risk assessment (CHRA) was conducted. The CHRA was carried out according to guidelines from DOSH under Use and Standard of Exposure of Chemicals Hazardous to Health (USECHH), 2000 Regulations. The assessment involving site visit, observation on handling chemicals by laboratory staff, reviewing lab manual and other relevant documents. Overall, 10 work units with total 108 chemicals managed to be assessed. Result found that risk of chemicals are significant either C2 or C3. There are four work units were marked C2 by having significant risk and adequately controlled. The other six work units fall under C3 which having significant risk but inadequately controlled. Based on the conclusion, CHRA were conducted to reduce the risks of chemical exposure among laboratory staff. This study can be useful to implement CHRA program in laboratories to assess the risk of chemical exposure and required control measures for the protection of laboratory staff.